2017
DOI: 10.1007/s10620-017-4643-6
|View full text |Cite
|
Sign up to set email alerts
|

Specialist Endoscopists Are Associated with a Decreased Risk of Incomplete Polyp Resection During Endoscopic Mucosal Resection in the Colon

Abstract: Background Endoscopic experience is known to correlate with outcomes of endoscopic mucosal resection (EMR), particularly complete resection of the polyp tissue. Whether specialist endoscopists can protect against incomplete polypectomy in the setting of known risk factors for incomplete resection (IR) is unknown. Aims We aimed to characterize how specialist endoscopists may help to mitigate the risk of IR of large sessile polyps. Methods This is a retrospective cohort study of patients who underwent EMR at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Experts were successful in 76% of cases while non-experts were successful in only 40%[ 34 ]. A retrospective study showed that the performance of resection by an expert endoscopist was protective against incomplete resection in the presence of other risk factors for incomplete resection [adjusted OR 0.13, 95%CI (0.04-0.41)][ 35 ]. The CARE study demonstrated that the rate of incomplete resection in polyps that, in the judgment of the endoscopist, were assumed to be completely removed was high (10.1%), increased with polyp size, and was highly dependent on the endoscopist.…”
Section: Why Is An Expert Endoscopist More Effective?mentioning
confidence: 99%
“…Experts were successful in 76% of cases while non-experts were successful in only 40%[ 34 ]. A retrospective study showed that the performance of resection by an expert endoscopist was protective against incomplete resection in the presence of other risk factors for incomplete resection [adjusted OR 0.13, 95%CI (0.04-0.41)][ 35 ]. The CARE study demonstrated that the rate of incomplete resection in polyps that, in the judgment of the endoscopist, were assumed to be completely removed was high (10.1%), increased with polyp size, and was highly dependent on the endoscopist.…”
Section: Why Is An Expert Endoscopist More Effective?mentioning
confidence: 99%
“…In one report, at least 100 colorectal EMR procedures were required to attain adequately high rates of technical success (14). Complex polypectomies performed by specialist endoscopists are associated with better outcomes including a lower risk of incomplete resection (15, 16). However, what constitutes appropriate training in advanced resection techniques is not widely accepted.…”
Section: Training: Expertise In Colonoscopy Is Not the Same As Expertmentioning
confidence: 99%
“…What has become clear, however, is that incomplete resection is associated with an increased risk of lesion recurrence and that this is less likely to occur if the resection is performed by a specialist endoscopist. A retrospective study of 257 patients with 269 polyps demonstrated the protective effect of a specialist endoscopist, and the odds ratio for incomplete resection was 0.13 (CI 0.04–0.41) 22 . Whilst there will be continuing debate as to what defines an ‘expert’, this is not an unexpected finding, and it is clear that whilst EMR is not as technically demanding as ESD, it should be performed by endoscopists who have been trained in the technique and who perform such resections on a regular basis with audited outcome data.…”
Section: Making Resection More Effective: Reducing Recurrence Risk Afmentioning
confidence: 99%
“…It is possible to predict the risk of lesion recurrence, and larger polyps carry an increased risk of incomplete resection or lesion recurrence 7 , 22 . Likewise, flat laterally spreading lesions or a poor lift also increases the complexity of resection and increases risk 7 , 22 . The Sydney EMR recurrence tool (SERT) can be used to predict the risk of adenoma recurrence.…”
Section: Making Resection More Effective: Reducing Recurrence Risk Afmentioning
confidence: 99%